New species and combinations in Meniscium (Thelypteridaceae) - Fernandes, Rozijane Santos; Yesilyurt, Jovita Cislinski; Salino, Alexandre (Phytotaxa, 2014)
Two new species of Meniscium, M. divergens and M. triangularis are described and illustrated. In addition, four new combinations, M. cocleanum, M. hostmannii, M. lanceum, and M. maxonianum and one lectotypification—M. hostmannii—are made in Meniscium.